Gonad Maturation of Clown Loach (Botia macracanthus) in Pond - Irzal Effendi; T. Prasetya; Agus Oman Sudrajat; N. Suhenda; K. Sumawidjaja (Jurnal Akuakultur Indonesia)
The objective of this research is to know the gonad maturation of clown loach {Botia macracanthus) reared in pond. Two groups contain 4 female broodstock; I) carried and II) non-carried egg broodstock were reared in two separated hapas which placed in pond. Each hapa was also stocked nine males. The fish were fed pellet (32,33% protein) 10% biomass, daily in three times. After 20 days, the broodstocks were implanted by LHRH-a 100 u.g/kg of body weight. In the group I, diameter of egg in gonad were developed from 1,028 mm at the beginning of implantation to 1,071 and 1,106 mm at day of 15 and 30 after implantation respectively. In the group II, only one female has developed her gonad successfully. The egg was developed to 0,937 and 1,026 mm after 15 and 30 day implantation respectively.